Local-non-local: Re-appropriating co-creation methods for remote collaboration - Eskilsson, Robin; Rifat, Mumtaheena (My University, 2021)
Participatory community development projects (PCDP) that conventionally relied on face-to-face co-creation activities have been greatly affected by the lock-downs and travel restrictions caused by the COVID-19 pandemic. These restrictions have forced co-creators to rethink and find an alternative practice that can facilitate remote collaborations. This paradigm shift leads to investigating how these projects can be run and developed even with the crisis that affects mobility and presence on-site. Increased online interactions and remote work possibilities that emerge from the current pandemic create new ground to investigate co-creation practices. Contemporary literature and research discuss the process of collaboration in remote work culture and the digitalization of co-creation. However, there is a gap between digitalized remote facilitation and co-creation in cross-cultural PCDP. Research on methods of co-creation and analysis of the roles and ethical responsibilities of co-creators collaborating remotely in PCDP can bridge this gap. Content analysis of conventional methods of co-creation and case studies of architectural design studios working remotely in PCDP introduced the possibility of re-appropriating co-creation methods for remote collaboration. Chalmers Reality Studio 2021 (RS) acted as a ground for co-developing a prototype of re-appropriation. The studio included remote collaboration with co-creators from local communities, Community Based Organizations, Architectural Non-Governmental Organizations in seven contexts of PCPD worldwide. The multitude of collaborators contributed to the evaluation of re-appropriation from both a local and non-local perspective. This thesis contains thoughts and reflections that identify different aspects of remote collaboration and the role of co-creators in PCDP through reflexive written and visual essays. In addition, the re-appropriated methods co-developed with RS, visual models of re-appropriation, participation, and facilitation can aid future co-creators to engage in PDCP. To contribute more than just conceptually, a prototype for a digital platform–Placemakers Kit is designed for the accessibility of anyone collaborating in a PCDP. The Placemaker’s Kit harbors the methods and case studies of co-creation from RS and welcomes future co-creators to share their stories on the platform. With a speculative scenario, we show the applicability of the Placemaker’s Kit and our hope for future opportunities of remote collaboration in PCDP beyond the limitations caused by the pandemic.
Keywords: Co-creation, co-design, community development, design methods, remote collaboration, digital platform